Deskripsi Kemampuan Guru dalam Memberikan Motivasi Siswa pada Keterampilan Membaca di SD Negeri 09 Kecamatan Sungai Ambawang - Tohir, M.; Fatmawati, Risdiana Andika; Suriyana, Suriyana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The background of this study is based on the low literacy level in Indonesia, which is reflected in the low ranking in the international literacy index. Teachers have a vital role as a motivator who can shape students' reading habits and increase their interest in reading. This study aims to analyze the ability of teachers to motivate students on reading skills at SD Negeri 09, Sungai Ambawang District. This study uses a qualitative approach with data collection techniques through interviews and observations of eight teachers and student behavior in grade IV of SD Negeri 09 Sungai Ambawang. Data analysis is carried out by the stages of data reduction, presentation of data in narrative form, and verification for validation of results. The results of the study show that although teachers have provided motivation at the beginning of learning, most of them are not optimal in asking students to read in front of the class, providing encouragement to read at the end of the lesson, and reminding students to make reading a habit. In addition, teachers tend not to remind the importance of taking advantage of free time to read. This study highlights the importance of the role of teachers in fostering a sustainable reading culture and making a significant contribution to improving student literacy.